2009
DOI: 10.2190/et.38.2.h
|View full text |Cite
|
Sign up to set email alerts
|

Course Crash in Hybrid Space: An Exploration and Recommendations for Virtual Course Space

Abstract: Understanding what hybrid space is, much less understanding what happens in that virtual realm, can raise difficult questions. For example, our campus's question “How do we define hybrid?” has kept us busy and guessing for over a year now. In this article, we offer a few suggestions on how to proceed with hybrid issues, including how to deal with hybrid space during a “crash,” which we experienced across our four course case study. We combine qualitative narrative and quantitative analysis to reach some prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…However, as noted in the report, web-enhanced courses typically included additional learning time and instructional units; hence, the observed benefits were likely to stem from added instruction, as opposed to the advantages of online media. The increased workload associated with web-enhanced instruction is referred to as the ''course and a half syndrome'' (Gerard et al, 2009).…”
Section: Is Hybrid Instruction Effective?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, as noted in the report, web-enhanced courses typically included additional learning time and instructional units; hence, the observed benefits were likely to stem from added instruction, as opposed to the advantages of online media. The increased workload associated with web-enhanced instruction is referred to as the ''course and a half syndrome'' (Gerard et al, 2009).…”
Section: Is Hybrid Instruction Effective?mentioning
confidence: 99%
“…Internet-based course management systems (CMS), such as Blackboard, Moodle, or Canvas, and publisher-provided course-packs, such as MyPsychLab, WileyPLUS, or LaunchPad, have made it feasible to teach courses fully or partially online by providing virtual classroom spaces and ready-made online modules to accompany textbook chapters. Incorporating these digital tools into course design provides students with opportunities to develop technological skills (Gerard, Gerard, & Casile, 2009; Powers, Brooks, McCloskey, Sekerina, & Cohen, 2013). Whether this translates into more effective teaching and learning remains controversial, especially for introductory-level survey courses where students may lack adequate preparation to utilize the tools effectively (El Mansour & Mumpinga, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In this class, we reversed that and it was a lot harder as a result" (Survey Monkey). Gerard et al (2010) observed in their study of hybrid instruction that "most students desire a relatively high degree of structure with instructor feedback as to what is right and wrong," even preferring the lecture format over the instructor's role as facilitator (p. 169). In our case, the lack of level-specific grammar and course-specific vocabulary left the students feeling inadequate during the communicative group activities such as scenarios and role-plays.…”
Section: Curriculum and Delivery Formatmentioning
confidence: 99%
“…This leads to a piecemeal approach in many departments where interested and enthusiastic instructors develop courses that might or might not be part of an overarching framework. This approach means that students take many courses that look and feel different from each other and demand varying workloads (Gerard et al 2010). For this reason, it is imperative that the foreign language teaching profession develop best practices for blended and hybrid courses that include a repository of current materials, testing tools that take the new format into consideration, and standards that are adjusted to the new modality.…”
Section: Final Thoughtsmentioning
confidence: 99%
See 1 more Smart Citation